From Rural Education to Countryside Education: advances and challenges in Brazil - Yatim, Leila; Martins, Fernando José (Emerging Trends in Education, 2024)
Brazil shared the nomenclature of rural education, as is common in most countries, effectively in Latin America. There was a nominal change to Countryside Education, in the field of social practices and in the official, documental and formal field in the educational system. This article seeks to highlight the foundations for such a change, which finds its basis in rural social movements. The work is carried out by a bibliographic review on the subject, and a documental review, both in official documents of the Brazilian State, and in the documents issued by the collective organization of the movement “for a rural education”. The change is qualitative, because from it, a perspective of the right to education for rural people is inserted in the praxis of rural schools, the relationship of the school with the community, with the territory and with local development. It is possible to conclude that the change of nomenclature is not enough to overcome the inequalities of rural education, but rather a movement.
Keywords: rural education; countryside education; educational policies; social movements; Brazil